Routing Protocols and Mobility Predictions for UAV Data Collection From Agricultural Sites: A Survey - Khemis Ben Samuel; Stephen D. Wolthusen; Julianne Sansa Otim; Roseline Nyongarwizi Akol; Mary Nsabagwa (IEEE Access)
Unmanned Aerial Vehicles (UAVs), also known as drones, have found applications in precision agriculture owing to their agility and remote access. However, because of battery, bandwidth and environmental constraints, UAV’s networks experience intermittent links and packet drops. These constraints can either force the UAV to abort its mission or increase packet drops. Therefore, there is a need to improve routing protocols and UAV path planning. This work reviewed routing protocols such as reactive and hybrid as well as mobility predictions such as regressive and Markov models with the central argument of topology control and path optimizations. Optimizations minimize the coverage time and energy consumption. As routing protocols operate on the network layer, this review analyses articles that include cross-layer issues, modelling, and predictions. This article also examined QoS metrics (such as bandwidth and link quality), antenna selection and placement on the UAV and the methods used to validate routing protocols. In this work, UAV’s path optimizations consider crop locations, the appropriate placement of ground sensor nodes and how neighbouring UAVs are controlled for efficient data collection and relay. Analysis of the collected data can improve crop health, cultivation management, livestock monitoring, and reduction on operational cost. Therefore, this work resolved that by predicting the topology change, link-lifetime, and residual energy, the routing protocol can reduce retransmission and packet drops, thereby enhancing network longevity.